Intermediaries in international trade: Direct versus indirect modes of export - Andrew B. Bernard; Marco Grazzi; Chiara Tomasi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2010)
This paper contributes to the relatively new literature on the role of intermediaries in international trade. Using Italian firm-level data, we document significant differences between exporters of different types and highlight the role of country-specific fixed cost in the choice of direct versus indirect modes of export. Recent theoretical work suggests that intermediaries are typically providing solutions to country-specific fixed costs. Our empirical results largely confirm this relationship. Measures of country fixed costs are positively associated with intermediary exports both in the aggregate and within firms. In contrast, proxies for variable trade costs are largely not correlated with differences between direct and indirect exports.
Keywords: D22; F14; L22; L23; 330; heterogeneous firms; international trade; intermediation; wholesalers; Exportwirtschaft; Vermittlungstätigkeit; Unternehmensorganisation; Großhandel; Transaktionskosten; Italien